2014
DOI: 10.1177/0018720814523066
|View full text |Cite
|
Sign up to set email alerts
|

Using Scanpaths as a Learning Method for a Conflict Detection Task of Multiple Target Tracking

Abstract: Implementing experts' scanpaths into novices' active learning process shows promise in enhancing training effectiveness and reducing training time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 17 publications
0
31
0
Order By: Relevance
“…As a result, it was recommended that practice-based training be utilized over traditional frontal teaching methods when teaching nontechnical skills. Similarly, a study by Kang and Landry [18] explored using scanpaths as a learning method for air traffic conflict detection and showed significant performance increases and confidence boosts in students. A 2015 case study by Airservices Australia, detailed in [19], demonstrated the benefits of updated simulation systems with new features, such as recording, pausing, and replaying training sessions with both video and audio.…”
Section: Literature Reviewmentioning
confidence: 99%
“…As a result, it was recommended that practice-based training be utilized over traditional frontal teaching methods when teaching nontechnical skills. Similarly, a study by Kang and Landry [18] explored using scanpaths as a learning method for air traffic conflict detection and showed significant performance increases and confidence boosts in students. A 2015 case study by Airservices Australia, detailed in [19], demonstrated the benefits of updated simulation systems with new features, such as recording, pausing, and replaying training sessions with both video and audio.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Analyzing visual scanning patterns and dynamic characteristics can help in understanding individuals’ underlying mental processes and scanning strategies; thus, these analyses can help in minimizing potential accidents and in designing appropriate human‐machine interfaces. To date, although there have been many visual scanning studies using dynamic glance measures (e.g., transitions of eye fixation) in aviation (Harris, Glover, & Spady, , Haslbeck & Zhang, , Kang & Landry, , Marchitto, Di Stasi, & Cañas, ), relatively few studies have explored drivers’ visual scanning patterns and dynamic characteristics. Underwood, Chapman, Brocklehurst, Underwood, and Crundall () identified driver's three scanning patterns (i.e., single/two/three‐fixation scanpaths) while driving on different road types (i.e., rural, suburban and dual‐carriageway).…”
Section: Introductionmentioning
confidence: 99%
“…Fourth, previous research in image analysis shows a strong connection between visual scan patterns and cognitive processing [21]. Some examples are found in radiology [54] - [56], chess [36] , [52], air traffic control [41]- [43] and reading [57] - [59]. In these activities, researchers found that although participants were asked to perform the same task, for example, playing chess, reading, or finding an abnormality in a chest X-ray, their visual scan patterns became more efficient as their level of experience increased [44].…”
Section: Visual Perception and Eye-trackingmentioning
confidence: 95%
“…Third, different eye-tracking studies in radiology [38], computer tomography [39], aircraft inspection [40], and in air traffic control [41] had shown that less experienced observers benefit from learning where expert observers looked when they performed their visual inspection task.…”
Section: Visual Perception and Eye-trackingmentioning
confidence: 99%
See 1 more Smart Citation